2017
DOI: 10.1093/jat/bkx034
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity From Intravenous Use of the Tricyclic Antidepressant Tianeptine

Abstract: Tianeptine (7-[([3-chloro-6,11]-dihydro-6-methyldibenzo[c,f][1,2]thiazepin-11-yl) amino] heptanoic acid S, S dioxide) is a tricyclic compound prescribed as an antidepressant in European countries, but is not currently approved for use in the United States. There are few published case reports of tianeptine intoxication. Presented is the first case of acute toxicity associated with the intravenous use of tianeptine. A 36-year-old male intentionally injected tianeptine powder intravenously to "help him see into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…When sold as dietary supplement, its use might even be a blind spot for early warning systems (Evans-Brown and Sedefov 2018;Griffiths, Evans-Brown, and Sedefov 2013). However, as several case reports highlight the danger of the potentially fatal misuse of tianeptine (Bakota et al 2018;Dempsey et al 2017;Proença et al 2007;Rushton et al 2020), increasing awareness is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…When sold as dietary supplement, its use might even be a blind spot for early warning systems (Evans-Brown and Sedefov 2018;Griffiths, Evans-Brown, and Sedefov 2013). However, as several case reports highlight the danger of the potentially fatal misuse of tianeptine (Bakota et al 2018;Dempsey et al 2017;Proença et al 2007;Rushton et al 2020), increasing awareness is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports showed that tianeptine toxicity mimicked opioid toxicity and that naloxone was an effective therapy ( 6 , 7 ). Tolerance to tianeptine and withdrawal have been reported ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those with coexposures to other substances are more likely to have severe outcomes than those with tianeptine-only exposures (El Zahran et al, 2018). Case reports from the literature suggest acute toxicity from tianeptine use may be successfully treated with the use of naloxone (Ari et al, 2010; Dempsey et al, 2017).…”
Section: Tianeptine Intoxicationmentioning
confidence: 99%